TAHAPAN PEMBENTUKAN BRAND AWARENESS NFRT LABEL (NEFERTITI) SEBAGAI EFFORTLESS FASHION MELALUI MEDIA SOSIAL INSTAGRAM - Fidya Zahra Afifah; Yanti Setianti; Heru Ryanto Budiana (Universitas Merdeka Malang, 2019)
AbstractThe vastly dynamic movement of fashion industry where many brands are converting to digital marketing, is seen as an opportunity for Indonesian local brands such as NFRT Label (Nefertiti) to build brand awareness. NFRT Label is a woman clothing line that was found in 2011. With their identity as